Radio recombination lines: Their Physics and Astronomical applications - Gordon, M.A. (Springer, 2017)
This book is a tourist’s guide to the world of Radio Recombination Lines. It contains three divisions: a history of their discovery, the physics of how they form and how their voyage to us influences their spectral profiles, and a description of their many astronomical contributions to date. The appendix includes supplementary calculations that may be useful to some astronomers. This material also includes tables of line frequencies from 12 MHz to 30 THz (λ =10 μ m) as well as FORTRAN computer code to calculate the fine-structure components of the lines, to evaluate radial matrix integrals, and to calculate the departure coefficients of hydrogen in a cosmic environment. It also describes how to convert observational to astrophysical units. The text includes extensive references to the literature to assist readers who want more details.